2009
DOI: 10.1158/1078-0432.ccr-08-2373
|View full text |Cite
|
Sign up to set email alerts
|

Satraplatin, an Oral Platinum, Administered on a Five-day Every-Five-Week Schedule: a Pharmacokinetic and Food Effect Study

Abstract: Purpose: The study aimed to assess the pharmacokinetic behavior of satraplatin under fasted and fed conditions, and its safety and preliminary antitumor activity in adults with advanced solid tumors. Experimental Design: Satraplatin was administered orally at 80 mg/m 2 once daily with prophylactic antiemetics for 5 consecutive days every 5 weeks. Patients were randomized to receive day 1 and day 5 doses of satraplatin in either the fed or fasted state, the order being reversed for cycle 2. Pharmacokinetic samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(31 reference statements)
2
10
0
1
Order By: Relevance
“…Pharmacokinetic analyses using atomic absorption spectroscopy performed in two adult phase I trials showed mean plasma UF AUC was 0.28 ± 0.1 and 0.249 ± 0.044 mcg/ml*h and mean C max was 0.047 ± 0.005 and 0.052 ± 0.016 mcg/ml at doses of 60–80 mg/m 2 /dose once daily for 5 days . Similar results were also observed in adult studies that used inductively coupled plasma mass spectrometry to measure ultrafilterable platinum (AUC 0–24 0.419–0.466 mcg/ml*h and C max 0.054–0.057 mcg/ml) . Although two of the adult studies used a similar assay for measuring plasma UF platinum, the adult and pediatric pharmacokinetic evaluations were not performed in the same laboratory, and the possibility that the observed differences in pharmacokinetic parameters were due to differences in the analytical assay cannot be completely excluded.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Pharmacokinetic analyses using atomic absorption spectroscopy performed in two adult phase I trials showed mean plasma UF AUC was 0.28 ± 0.1 and 0.249 ± 0.044 mcg/ml*h and mean C max was 0.047 ± 0.005 and 0.052 ± 0.016 mcg/ml at doses of 60–80 mg/m 2 /dose once daily for 5 days . Similar results were also observed in adult studies that used inductively coupled plasma mass spectrometry to measure ultrafilterable platinum (AUC 0–24 0.419–0.466 mcg/ml*h and C max 0.054–0.057 mcg/ml) . Although two of the adult studies used a similar assay for measuring plasma UF platinum, the adult and pediatric pharmacokinetic evaluations were not performed in the same laboratory, and the possibility that the observed differences in pharmacokinetic parameters were due to differences in the analytical assay cannot be completely excluded.…”
Section: Discussionsupporting
confidence: 67%
“…The toxicity profile in our pediatric population was similar to that in adults, and myelosuppression was the DLT. Myelosuppression was delayed with a median neutrophil nadir in cycle 1 occurring on day 27 (range 5-42,) and platelet count nadir on day 27 (range [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. This was similar to adults where median neutrophil nadir occurred on day 21 (range 2-63) and median platelet count nadir occurred on day 21 (range 2-64).…”
Section: Discussionmentioning
confidence: 76%
“…This ultimately results in formation of the highly cytotoxic metabolite JM118 being not a substrate of OATP5A1 (data not shown). However, the narrow dose window of 1.25–5 μM satraplatin for the action of OATP5A1 matches closely the peak plasma concentrations of this drug, and relatively small changes in cellular resistance in this range may result in profound clinical effects 27. This mechanism of chemoresistance in highly refractory SCLC cell lines may be induced by the potential OATP substrate etoposide that is commonly used in conjunction with cisplatin for standard chemotherapy 2.…”
Section: Discussionmentioning
confidence: 98%
“…Sokat ezek közül már klinikai vizsgálatokban tesztelnek. A célzott terápiás szerek egyre bővülő palettája mellett citosztatikumok (például satraplatin) is szerepelnek a vizsgált gyógyszerek között [65]. A második generációs (irreverzíbilis) tirozinkináz-inhibitorok köre még jelentősen bővül, de más hatásmechanizmusú gyógyszerek (például hisztondeacetilázok) tumorellenes hatékonysá-gát is vizsgálják [66,67,68].…”
Section: Következtetésekunclassified